Fighting Corruption the Celtel Way : Lessons from the Front Line - Ibrahim, Mohamed (World Bank, Washington, DC, 2012)
Celtel is dedicated to making life better. In our eyes this means ensuring a sustainable business to continue the infrastructure investment essential to Africa's development. And it means doing so in a fully transparent manner, including publishing what we pay to Governments and state-owned enterprises : this amounted to some 35 percent of Celtel's revenue in 2005. The Celtel story shows emphatically that it is possible, if not always easy, to run a successful clean business in Africa which can benefit all stakeholders and help to enable development.